Medical abortion in Nepal: A qualitative study on women's experiences at safe abortion services and pharmacies - Rogers, Claire; Sapkota, S.; Paudel, R.; Dantas, Jaya A R (BMC, 2019)
© 2019 The Author(s). Background: Although Nepal legalised abortion in 2002, a significant number of women continue to access unsafe abortions. An estimated 60% of all abortions performed in 2014 were unsafe, with unsafe abortion continuing to be a leading contributor to maternal mortality. Despite medical abortion access being solely permitted through government accredited safe abortion services, medical abortion pills are readily available for illegal purchase at pharmacies throughout the country. Methods: Utilising an Assets Focused Rapid Participatory Appraisal (AFRPA) research methodology, underpinned by a health information pyramid conceptual framework, this qualitative exploratory study collected data from in-depth, open-ended interviews. The study explored the medical abortion and sexual and reproductive health experiences of ten women who accessed medical abortion through an accredited safe abortion service, and ten women who accessed unsafe medical abortion through pharmacies. Results: Thematic content analysis revealed emerging themes relating to decision-making processes in accessing safe or unsafe medical abortion; knowledge of safe abortion services; and SRH information access and post-abortion contraceptive counselling. Findings emphasised the interconnectivity of sexual and reproductive health and rights; reproductive coercion; education; poverty; spousal separation; and women's personal, social and economic empowerment. Conclusions: While barriers to safe abortion services persist, so will the continued demand for medical abortion provision through pharmacies. Innovated and effective harm reduction implementations combined with access and information expansion strategies offer the potential to increase access to safe medical abortion while decreasing adverse health outcomes for women.